Comparative study between direct analysis in whole blood, oral fluid, and declaration of consumption for the prevalence of nonsteroidal anti‐inflammatory drugs and acetaminophen in ultratrail runners. Issue 1 (2nd October 2022) - Mashal, Mohammad Shafiq; Bevalot, Fabien; Citterio‐Quentin, Antony; Sallet, Pierre; Nazari, Qand Agha; Guitton, Jérôme; Machon, Christelle
Abstract: Ultratrail running is a sport with growing number of adherents. To complete ultratrail despite physical issues such as joint and muscle pain, many runners use nonsteroidal anti‐inflammatory drugs (NSAIDs) and acetaminophen. Studies asking participants about their consumption of drugs during ultratrail revealed a prevalence of NSAIDs and acetaminophen up to 70% and 25%, respectively. The aims of the present study were to determine the prevalence of NSAIDs and acetaminophen for 81 runners during the 2021 Ultratrail du Mont Blanc® (UTMB®) using direct analysis of dried blood spots (DBS) and oral fluid (OF) and to compare results with the declaration of consumption by runners; this is to identify the most relevant method to study the prevalence of drugs. Our results show a prevalence of NSAIDs of 46.6% using DBS, 18.5% using OF, and 13.8% based on a questionnaire. Prevalence of acetaminophen were 30.1%, 30.9%, and 22.5% using DBS, OF, and questionnaire, respectively. From this study, we conclude that the analysis of drugs directly in DBS is the most relevant tool to determine the prevalence in ultratrail events. Abstract : In the present work, the prevalence of the use of NSAIDs and acetaminophen in ultratrail was studied using three tools: direct analysis of dried blood spots (DBS), direct analysis of oral fluid (OF), and a questionnaire filled by runners. Comparative results showed that the analysis of drugs in DBS is the most relevant tool to determine the prevalence in ultratrail events.